Hemophagocytic Lymphohistiocytosis in Adults: Low Incidence of Primary Neoplasm as a Trigger in a Case Series from Turkey - (:unkn) unknown (PAGEPRESS PUBL, 2018)
Hemophagocytic Lymphohistiocytosis (HLH) is an indicator of an exaggerated immune response and eventually adverse outcomes. This study aimed to investigate the clinical and laboratory features and outcomes of patients with HLH. The medical records of 26 HLH adult patients (>= 16 years of age) were retrospectively analyzed. Gender, age, the duration of fever, time to diagnosis, etiology and laboratory data were extracted from the records. The mean age was 38 +/- 18 years, and 15 (58%) patients were female. A total of nine cases had infectious diseases; four cases had rheumatologic diseases, three cases had hematological malignancies while nine cases could not have a definitive diagnosis. The median time to detection of HLH was 20 days (IQR: 8-30 d). Of the 25 patients, 11 (44%) died. The erythrocyte sedimentation rates of the surviving and non-surviving patients were 39 +/- 22 mm/h and 15 +/- 13 mm/h, respectively. When a long-lasting fever is complicated by bicytopenia or pancytopenia (especially), clinicians should promptly consider the possibility of HLH syndrome to improve patients' prognosis.
Keywords: Hemophagocytic lymphohistiocytosis; Ferritin; Cytopenia; Fever of unknown origin; HLH-2004; HLH